New Medical Device and Therapeutic Approvals in Otolaryngology: State of the Art Review of 2019 - Anais Rameau MD, MPhil; Robert Stephen Hong MD, PhD; Hamid Djalilian MD; Isaac David Erbele MD; Katie M. Phillips MD; Robson Capasso; Austin S. Rose MD, MBA; Michael Joel Brenner MD; Peter Luke Santa Maria MBBS, PhD (OTO Open, 2020)
Objective To review new devices and drugs relevant to otolaryngology–head and neck surgery that were approved by the US Food and Drug Administration (FDA) in 2019. Data Sources Approval notifications for 2019 were extracted from the ENT (ear, nose, and throat) and general and plastic surgery sections of the FDA’s medical devices and therapeutics listings. Review Methods New therapeutics and medical devices identified from the query were analyzed by members of the American Academy of Otolaryngology–Head and Neck Surgery’s Medical Devices and Drugs Committee. Technologies were assessed by 2 independent reviewers to ascertain relevance to otolaryngology, prioritized, and classified to subspecialty field with critical review based on extant scientific literature. Conclusions Query of the FDA drug and device database returned 105 ENT devices (50 cleared, 55 with premarket approval, and 0 de novo), 543 general and plastic surgery devices (372 cleared, 170 with premarket approval, and 1 de novo), and 46 new otolaryngology-relevant drug approvals that occurred in 2019. Advances spanned all subspecialty areas with otology predominating, primarily due to hearing-related technologies. While scientific evidence was available for all new devices, there was significant heterogeneity in rigor of supporting scientific data. Implications for Practice Technological and pharmaceutical innovation is an important catalyst for advances in the surgical specialties. Familiarity with new devices and therapeutics in otolaryngology–head and neck surgery ensures that clinicians keep abreast of developments with potential to improve prevailing standards of care.